Physiological responses of a halophytic shrub to salt stress by Na2SO4 and NaCl: oxidative damage and the role of polyphenols in antioxidant protection - Reginato, Mariana Andrea (2014)
Salt stress conditions lead to increased production of reactive oxygen species (ROS) in plant cells. Halophytes have the ability to reduce these toxic ROS by means of a powerful antioxidant system that includes enzymatic and non-enzymatic components. In this research, we used the halophytic shrub Prosopis strombulifera to investigate whether the ability of this species to grow under increasing salt concentrations and mixtures was related to the synthesis of polyphenolic compounds and to the maintenance of leaf pigment contents for an adequate photosynthetic activity. Seedlings of P. strombulifera were grown hydroponically in Hoagland's solution, gradually adding Na2SO4 and NaCl separately or in mixtures until reaching final osmotic potentials of −1, −1.9 and −2.6 MPa. Control plants were allowed to develop in Hoagland's solution without salt. Oxidative damage in tissues was determined by H2O2 and malondialdehyde content. Leaf pigment analysis was performed by high-performance liquid chromatography with ultraviolet, and total phenols, total flavonoids, total flavan-3-ols, condensed tannins, tartaric acid esters and flavonols were spectrophotometrically assayed. Treatment with Na2SO4 increased H2O2 production and lipid peroxidation in tissues and induced a sharp increase in flavonoid compounds (mainly flavan-3-ols) and consequently in the antioxidant activity. Also, Na2SO4 treatment induced an increased carotenoid/chlorophyll ratio, which may represent a strategy to protect photosystems against photooxidation. NaCl treatment, however, did not affect H2O2 content, lipid peroxidation, pigments or polyphenols synthesis. The significant accumulation of flavonoids in tissues under Na2SO4 treatment and their powerful antioxidant activity indicates a role for these compounds in counteracting the oxidative damage induced by severe salt stress, particularly, ionic stress. We demonstrate that ionic interactions between different salts in salinized soils modify the biochemical and morpho-physiological responses of P. strombulifera plants to salinity.